(untitled) (Theatrum historiae, 2017)
The study focuses on the life of writer Vlasta Javořická, her husband František Zezulka, the director of significant meat factory on the border of Bohemia and Moravia, and their youngest daughter Václava after the 25th of February 1948. A life story of this woman, so active in culture space, and of her family shows many phenomenons typical for the period of Czech history after the establishing of the totalitarian communist regime. Her literary ability was very useful for her recording of the events of February 25th 1948 and following years.